การถ่ายทอดดนตรีพื้นเมืองล้านนาของเจ้าสุนทร ณ เชียงใหม่ - ทศพร จันทร์เลิศ (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
This research has the purposes to examine 1. the life history and work of Prince Sunthorn Na Chiangmai, 2. the development of traditional Lanna Music and 3. the transmission and the inheritance of Lanna traditional music of Prince Sunthorn Na Chiangmai. The results showed that Prince Sunthorn Na Chiangmai was born to and raised by the ruling family of Chiang Mai. He received Lanna and Thai traditional music training at an early age from the khum luang palace. After receiving an invitation from the Chiang Mai College of Dramatic Arts to serve as a Lanna traditional music specialist, Prince Sunthorn incorporated Thai traditional music practices to the teaching of salo ensemble. There he standardized instrument organization, ensemble setup, the sizes and tuning system of salo and sueng. This resulted in a theorization of the salo and sueng ensemble in terms of performance practices, instrumentation, ensemble setup and the notation of Lanna Traditional Music. He also initiated the installation of guitar tuning pegs into a sueng for a better tolerance of string tension.Prince Sunthorn Na Chiangmai taught Lanna traditional music to students majoring in Thai classical music and music instrument making. His teaching methods included juxtaposing between playing instruments and singing (noi siang) at a rudimentary level before proceeding to teaching basic, intermediate, and advanced pieces accordingly. He was noted for combining the Lanna traditional playing techniques with those of the Thai traditional music. The pedagogy conceived by Prince Sunthorn Na Chiangmai is still used today. The most prominent musical lineage of Prince Sunthorn Na Chiangmai consists of the Chiang Mai College of Dramatic Arts alumni who have become teachers in various campuses of the College of Dramatic Arts as well as in the local schools across Northern Thailand.